Case Report: foetal gastroschisis with ideal pregnancy outcomes under multidisciplinary treatment management - Liu, Shuhua; Qian, Jingyu; Li, Qiuru; Liu, Dehong; Zhang, Bin; Chen, Xianxia (Frontiers in Pediatrics, 2024)
Background: Gastroschisis has increased in recent years, however, complicated gastroschisis is associated with higher mortality, as well as higher health care costs and disease burdens from short-and long-term complications.A woman aged 25 years old at 37+1 weeks gestation (gravida 2; para 0) was admitted to the hospital because of foetal gastroschisis. Targeted quaternary ultrasound performed at our hospital showed that 34 mm of the abdominal wall was interrupted continuously , an intestinal echo with a range of approximately 88*50 mm was seen bulging outwards the local area close to the intestinal wall showed a 34*23 m anecho, and the foetus was measuring 2 weeks smaller than expected. After MDT including the maternal-foetal medicine, ultrasound, paediatric surgery, neonatal intensive care unit (NICU), and anaesthesiology departments, caesarean section was performed at 37+2 weeks. A baby boy was delivered, the small intestine, large intestine and stomach were seen outside of the abdomen, the abdominal cavity was excluded from the defect on the right side of the umbilical cord, the mesentery was shortened, and the intestinal tube had obvious oedema After paediatric surgical discussion, silo bag placement and delayed closure was performed, the placement process was smooth. One week following silo placement, the abdominal contents had been fully reduced below the fascia following daily partial reductions of the viscera,and the second stage of the operation was performed under general anaesthesia. The newborn was successfully discharged from the hospital 20 days after the operation and was followed up, with good growth, normal milk intake and smooth bowel movements.The diagnosis and treatment of complicated gastroschisis needs to be carried out under multidisciplinary team treatment. Delivery by cesarean section after 37 weeks is feasible.Immediate postpartum surgery is possible, and the choice of surgical modality is determined by the child's condition, emphasizing that it should be performed without adequate sedation under anaesthesia. A standardized postoperative care pathway appropriate to risk should be developed to optimize nutritional support and antibiotic use, and standardized enteral feeding practices should be sought with long-term follow-up.